A deteriorating model for the prediction of elastic modulus of the aging fiber reinforced polymer under complex environmental effects. Issue 3 (September 2020) - Luo, Yi; Xia, Senwei; Peng, Xinqian; Xu, Yuye
The fiber reinforced polymer is popularly applied for structural reinforcement and, however, usually suffers from long-term environmental effects, for example exposed to the ultraviolet radiation, alternating changes of moist-heat, and submerged in water chronically. As a result, the material aging and structural performance degradation are inevitable, which could eventually lead to the deterioration of mechanical behavior of fiber reinforced polymer, hence the attenuation or failure of repaired structures. It is very expensive and time consuming to use the experimental method to find out the aging patterns of fiber reinforced polymer. For fiber reinforced polymer with different volume fraction, the upper and lower limit of elastic modulus can be deduced by the energy principle. Combining this theory with tests, a semi-empirical deteriorating method can be used to analyze the change of fiber reinforced polymer mechanics behavior. And a series of empirical coefficients, determined by natural aging tests, are introduced. The coefficients are applied in the revised formula for the prediction of mechanics behaviors of fiber reinforced polymer. The elastic modulus of deteriorating fiber reinforced polymer is influenced by the fiber, the resin matrix, and the volume fraction of the fiber. For different fiber volume fraction, the experimental test is not the unique way to assess the durability of fiber reinforced polymer, as long as the laws of fiber aging, the laws of resin aging, and the fiber volume fraction are already known. The proposed model shows good agreement with the test results, hence can be used to predict the elastic modulus of aging fiber reinforced polymer, which can be utilized as references for engineering design and research in the future.